Revisiting the physiological effects of methylene blue as a treatment of cyanide intoxication. (2nd September 2018) - Haouzi, Philippe; Gueguinou, Maxime; Sonobe, Takashi; Judenherc-Haouzi, Annick; Tubbs, Nicole; Trebak, Mohamed; Cheung, Joseph; Bouillaud, Frederic
Abstract: Background: Although methylene blue (MB) had long been proposed to counteract the effects of cyanide (CN) intoxication, research on its mechanisms of action and efficacy has been abandoned for decades. Recent studies on the benefits of MB in post-anoxic injuries have prompted us to reexamine the relevance of this historical observation. Methods: Our study was performed in adult male Sprague–Dawley rats and on HEK293T epithelial cells. First, the effects and toxicity of MB (0–80 mg/kg) on circulation and metabolism were established in four urethane-anesthetized rats. Then nine rats received a lethal infusion of a solution of KCN (0.75 mg/kg/min) and were treated by either saline or MB, at 20 mg/kg, a dose that we found to be innocuous in rat and to correspond to a dose of about 4 mg/kg in humans. MB was also administered 5 min after the end of a sub-lethal exposure to CN in a separate group of 10 rats. In addition, ATP/ADP ratio, ROS production, mitochondrial membrane potential (Δψm) and cellular O2 consumption rate (OCR) were determined in HEK293T cells exposed to toxic levels of CN (200 µM for 10 min) before and after applying a solution containing MB (1–100 µM for 10 min). Results: Methylene blue was found to be innocuous up to 50 mg/kg. KCN infusion (0.75 mg/kg/min) killed all animals within 7–8 min. MB (20 mg/kg) administered at the same time restored blood pressure, cardiac contractility and limited O2 deficit, allowing all the animals to survive, without any significant methemoglobinemia. When administered 5 min after a non-lethal CN intoxication, MB sped up the recovery of lactate and O2 deficit. Finally, MB was able to decrease the production of ROS and restore the ATP/ADP ratio, Δψm as well as OCR of epithelial cells intoxicated by CN. Conclusions: The present observations should make us consider the potential interest of MB in the treatment of CN intoxication. The mechanisms of the antidotal properties of MB cannot be accounted for by the creation of a cyanomethemoglobinemia, rather its protective effects appears to be related to the unique properties of this redox dye, which, depending on the dose, could directly oppose some of the consequences of the metabolic depression produced by CN at the cellular level.